Občutljivost gliv kvasovk, osamljenih iz nadzornih kužnin bolnikov s hematološkimi malignimi boleznimi v obdobju 1992-2005 - Matos, Tadeja (Zdravniški vestnik, 2008)
Yeasts of the genus Candida are among the most, frequent causative agents of opportunistic infections. In the last decades, the increased incidence of fungal infections led to increased consumption of antifungal agents. Our studycompared the sensitivity of Candida albicans and Candida glabrata isolated in two time periods 1992-1996and 2003-2005. The aim of our study was to determine whether the sensitivity of yeasts changed due to increased consumption of antifungal agents. All isolates were isolated from surveillancespecimens of patients, hospitalized in the Department of Hematology, University Clinical Center Ljubljana. In all yeast isolates minimal inhibitory concentrations (MIC) of fluconazole, voriconazole, itraconazole and amphotericin B were determined using the E-test. Mann-Whitney's U test was used for statistical analysis. Statistical comparison generally indicated lower antifungal drug sensitivity of yeasts in years 1992-1996, in comparison to the period 2003-2005. MICs of all tested antifungal agents in C. albicans isolates were higher in years 1992-1996. Differences in MICs of itraconazole and voriconazole were observed in C. glabrata isolates. MIC.s of itraconazole were higher in years 1992-1996 and MICs of voriconazole were higher in years 20032005. However, no statistically significant differences in MICs of fluconazole and amphotericin B were observed. We have also studied the influence of antifungal prophylactic therapy on MIC.s of antifungal agents. For C. albicans the influence was shownfor fluconazole and amphotericin B, while we could not show any influencefor C. glabrata, most probably due to low member of is plates.
Keywords: Amfotericin B; Amphotericin B; Antifungal Agents; Antimikotiki; Candida; Candidiasis; Drug Therapy; Fluconazole; Flukonazol; glivice; Hematologic Neoplasms; Hematološke novotvorbe; Kandida; Kandidiaza; Microbial Sensitivity Tests; mikoze; Mikrobni, občutljivostni testi; občutljivost; Oportunistične infekcije; Opportunistic Infections